2018
DOI: 10.1038/s41598-018-29825-5
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle cutoff values for sarcopenia diagnosis using T10 to L5 measurements in a healthy US population

Abstract: Measurements of skeletal muscle cross-sectional area, index, and radiation attenuation utilizing clinical computed tomography (CT) scans are used in assessments of sarcopenia, the loss of skeletal muscle mass and function associated with aging. To classify individuals as sarcopenic, sex-specific cutoffs for ‘low’ values are used. Conventionally, cutoffs for skeletal muscle measurements at the level of the third lumbar (L3) vertebra are used, however L3 is not included in several clinical CT protocols. Non-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
395
4
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(418 citation statements)
references
References 39 publications
13
395
4
6
Order By: Relevance
“…There is a need to validate other lumbar or thoracic landmarks in relation to whole body values. Recent work in this area suggests there are moderate to strong correlations between L3 and other lumbar and thoracic landmarks (eg, L2, L4, L5, L1, T12, T11, and T10), but more development is required . Ordering CT scans is under the purview of the medical oncology clinic, which limits the degree of control over if and when a CT scan is acquired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need to validate other lumbar or thoracic landmarks in relation to whole body values. Recent work in this area suggests there are moderate to strong correlations between L3 and other lumbar and thoracic landmarks (eg, L2, L4, L5, L1, T12, T11, and T10), but more development is required . Ordering CT scans is under the purview of the medical oncology clinic, which limits the degree of control over if and when a CT scan is acquired.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in this area suggests there are moderate to strong correlations between L3 and other lumbar and thoracic landmarks (eg, L2, L4, L5, L1, T12, T11, and T10), but more development is required. [34][35][36] Ordering CT scans is under the purview of the medical oncology clinic, which limits the degree of control over if and when a CT scan is acquired. We included patients who had a CT on average 11 ± 39 days prior to completing a PG-SGA SF assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Quantifications of body composition were performed using a dedicated commercially available workstation (Aquarius 3D workstation, TeraRecon, San Mateo, CA, USA). The inferior surface of the third lumbar vertebra (L3) was selected as a landmark site for the measurement of VFA, subcutaneous fat area (SFA), and SMA based on following evidences: data from Framingham Heart Study showed that VFA and SFA obtained at L3 level were most strongly correlated with visceral and subcutaneous fat volume and cardiometabolic risk factors; SMA at L3 level showed best correlation with whole body skeletal muscle mass . CT slices were loaded onto the workstation and VFA, subcutaneous fat area (SFA), and SMA from a single CT slice of the L3 inferior surface margin were measured by applying predefined radiation attenuation cutoffs for subcutaneous fat (−190 to −30 HU), visceral fat (−150 to −50 HU), and skeletal muscle (−29 to +150 HU).…”
Section: Methodsmentioning
confidence: 99%
“…Sarcopenia (L3 SMI: male <45.4 cm 2 /m 2 ; female <34.4 cm 2 /m 2 ) and low SMD (L3 SMD: male <38.5 HU; female <34.3 HU) were defined using threshold derived from a cohort of healthy kidney donors. 18 Visceral obesity (VFA > 100 cm 2 ) was defined based on the guideline from Japan Society of the Study of Obesity. 21 Hypertension was defined as having documented hypertension diagnosis with the use of at least 1 antihypertensive drug.…”
Section: Definitions Of Sarcopenia Visceral Obesity and Comorbiditiesmentioning
confidence: 99%
“…We propose that using common pre-specified cut-off values to define sarcopenia might be more useful and better feasible than median values. Previously, European Sarcopenia consensus [1] and sarcopenia definition for American population by Derstine et al [2] determined cut-off values for sarcopenia for both European and American population. In Korean population, it was defined as 49 cm 2 m −2 for men and 31 cm 2 m −2 for women on L3 vertebra level muscle volume by KHANES study (Korean population, based on the Korea National Health and Nutrition Examination Study) [3].…”
mentioning
confidence: 99%